The arduous beginnings of EC reform - Rudolf Hrbek (Intereconomics, 1987)
The first step towards reform of the EC was taken when the Single European Act came into force in July of this year. What concrete decisions must the member states now take? What are their chances of being implemented?
Keywords: 330; European Community